Dampak Penggunaan Teknologi Informasi dalam Peningkatan Akurasi Laporan Keuangan pada Perusahaan Jasa di Indonesia - Judijanto, Loso (Jurnal Akuntansi Dan Keuangan West Science, 2024)
This study investigates the impact of information technology (IT) use on the accuracy of financial statements in service companies in Indonesia. Utilizing a quantitative research approach, data were collected from 50 service companies through a structured questionnaire, with responses measured on a Likert scale (1-5). The data were analyzed using SPSS version 26. Results indicate a significant positive relationship between IT use and financial statement accuracy. The correlation analysis revealed a strong association, while regression analysis confirmed that IT use is a significant predictor of financial statement accuracy. The findings underscore the importance of IT adoption in improving financial reporting accuracy, suggesting that service companies that invest in IT systems can significantly enhance the reliability and transparency of their financial data. Practical implications include the need for service companies to increase IT integration and employee training to capitalize on the benefits of IT in financial management fully.